Tanggung Jawab Komisaris Perusahaan Perseroan BUMN Ditinjau dari UU No 40 Tahun 2007 Tentang Perseroan Terbatas - Shafira Andiena Qoyyumi Permadi; Ariawan Ariawan (Cakrawala Repositori IMWI, 2023)
State-Owned Enterprises or SOEs, are business entities whose share ownership is mostly owned by the state and are also one of the business entities that support the country's economy. Apart from producing goods and/or services, the presence of SOEs can also be a means of employment for the workforce. In order to support the success of a business, BUMN has three important organs, namely the GMS, Directors and Commissioners. In Article 6 paragraph (2) of Law Number 19 of 2003 concerning State-Owned Enterprises it is said that "The Commissioners and Supervisory Board are fully responsible for the supervision of SOEs for the interests and objectives of SOEs". Regarding the Commissioners themselves, it is regulated in Article 27 to Article 33 of Law Number 19 of 2003 concerning State-Owned Enterprises. However, for SOEs companies in the form of Persero, the regulation is also subject to Law Number 40 of 2007 concerning Limited Liability Companies, so that this study uses normative legal research methods. The purpose of this research is expected to be a reference for readers to be able to add insight into the responsibilities of commissioners under the law. This journal will discuss the responsibilities of the company's commissioners in terms of the Limited Liability Company Law. The results of this study which can be concluded are, the Commissioner as an important organ in SOEs is fully responsible for supervising and providing advice to the Directors in carrying out the company's management activities.